2022
DOI: 10.1590/2317-1545v44261463
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and germination of Trichosanthes cucumerina L. seeds

Abstract: Trichosanthes cucumerina L. (Cucurbitaceae) is a traditional fruit vegetable grown by family farmers in the Amazon. This study aimed to evaluate seed maturation as a function of age and fruit morphological characteristics, and the effect of different temperatures on seed germination of accessions of the species. A completely randomized design was adopted in the maturation study, with five treatments (fruit age: 20, 30, 40, 50, and 60 days after anthesis - DAA) and four replications. Seed quality was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Brenan seeds were influenced by the maturity stage, as seeds from fruits with dark reddish brown and light brown colors showed higher germination speed index. Silva et al (2022) studying the maturation of seeds of Trichosanthes cucumerina L. (Cucurbitaceae) also found that the germination speed is increased with advancing age at fruit harvest. Temperature did not influence the germination percentage, with values ranging from 93.24 to 96.19%.…”
Section: Resultsmentioning
confidence: 99%
“…Brenan seeds were influenced by the maturity stage, as seeds from fruits with dark reddish brown and light brown colors showed higher germination speed index. Silva et al (2022) studying the maturation of seeds of Trichosanthes cucumerina L. (Cucurbitaceae) also found that the germination speed is increased with advancing age at fruit harvest. Temperature did not influence the germination percentage, with values ranging from 93.24 to 96.19%.…”
Section: Resultsmentioning
confidence: 99%